GEOLOGICAL STRUCTURE OF GOLD DISTRICTS OF VOLCANO-PLUTONIC BELTS IN EASTERN RUSSIA - Konstantinov M.M.; Politov V.K.; Novikov V.P.; Dankovtsev R.F.; Struzhkov S.F.; Cherkasov S.V.; Vakin M.E. (My University, 2002)
The deep structure of three gold districts (Yuzhno-Omolon, Gonzhin, and Tsentral'no-Kamchatsk) was reviewed on the basis of regional gravity data and seismic profiling. The formation of these ore districts was attributed to the Late Devonian, Upper Cretaceous, and Tertiary, respectively. The Yuzhno-Omolon gold ore district is situated in the Omolon median massif. It is made up of Middle-Late Devonian volcanics confined to the Kedon uplift of the basement. The gold-silver mineralization is represented by the large Kubaka deposit and a number of medium-sized and small deposits. On the whole, the deep structure of the ore district is characterized by the presence of a large deconsolidation zone of the earth's crust, whereas individual ore clusters are located over local positive gravity anomalies. The Gonzhin ore district is confined to the Umlekano-Ogondzhinsk volcano-plutonic belt. It is represented by a domelike uplift of Upper Cretaceous volcanics framed by peripheral grabens. The Pokrovskoe gold-silver deposit of the Gonzhin ore district has been explored, and several promising occurrences have been discovered in this ore district. The deconsolidation zone was established at a maximal depth of about 20-30 km. With increasing depth, it becomes cone-shaped, narrows, and reaches the upper mantle. Its axial part corresponds to a "zone of seismic transparency," which was revealed on the profile of the deep seismic sounding (DSS). The Tsentral'no-Kamchatsk ore district is confined to the Tsentral'no-Kamchatsk deep fault and the corresponding volcano-plutonic belt. The ore district is characterized by the development of Tertiary volcanics that fill a depression of a complex structure. The Aginsk gold-silver deposit and a number of promising occurrences are known in the ore district. Against the background of general deconsolidation of deep-seated zones of the volcano-plutonic belt, the ore district is characterized by a very extensive deconsolidation zone at a depth of about 25-40 km. This zone suggests the existence of a chamber of Tertiary magmatism.